Elevated follicular helper T Cells and expression of IL-21 in thyroid tissues are involved in the pathogenesis of Graves’ disease - Zhang, Jin; Ren, Meng; Zeng, Hua; Guo, Ying; Zhuang, Zhenwu; Feng, Zhimei; Yan, Haiyan; Xu, Mingtong; Liang, Weiwen; Yang, Chuan; Cheng, Hua; Ding, Helin; et al. (Immunologic research, 2015)
The follicular helper T cell (Tfh) and IL-21 have been shown to play an important role in many autoimmune diseases. However, less is known about their role in Graves’ disease (GD). This study aimed to investigate the expression of Tfhs and related factors (IL-21, IL-21R, CXCR5, and CXCL13) in GD thyroid tissues and to explore the effect of IL-21 on thyroid follicular cells (TFCs). The expression of Tfh-related factors in GD and normal thyroid tissues was validated using immunohistochemistry, real-time polymerase chain reaction and Western blotting. Confocal microscopy confirmed the presence of Tfh and IL-21R on CD4 + T-/CD19 + B cell in GD thyroid tissues. Furthermore, the effect of IL-21 on cAMP production in TFCs upon thyroid-stimulating antibody (TSAb) stimulation was also examined by an in vitro bioassay. The increased expression of Tfh-related factors was observed in GD thyroid tissues compared to control subjects. Confocal microscopy further confirmed the presence of Tfhs and the expression of IL-21R on CD4 + T cells and CD19 + B cells in GD thyroid tissues. Moreover, the expression of IL-21mRNA in GD thyroid tissues was correlated with the levels of thyroid autoantibodies. Additionally, IL-21 could indirectly promote cAMP production upon TSAb stimulation in TFCs when cooperating with lymphocytes, and GD TFCs were more sensitive to IL-21 stimulation than normal TFCs. There is increased expression of Tfhs and related factors (IL-21, IL-21R, CXCR5, and CXCL13) in GD thyroid tissues, and the expression of IL-21mRNA in GD thyroid tissues was found to correlate with the serum levels of thyroid autoantibodies and thyroid hormones. Moreover, IL-21 could indirectly enhance the biological activity of TFCs upon TSAb stimulation when cooperating with lymphocytes in vitro, particularly in GD TFCs, suggesting that Tfh and IL-21 might be involved in the pathogenesis of GD.